Most-liked and least-liked television personalities as perceived by selected students of the Araullo High School implications to education - Chaiyadej, Patcharintara 1948 (1975)
The primary purpose of this study was to look into the perceptions of randomly chosen high school students about their most-liked and least-liked television personality. Specifically the paper sought to determine who among the television personalities high school students like most or like least and how the students describe these personalilties.
Thesis (M.Ed.)--University of the Philippines
Keywords: Television audiences; Television and education